Rhinologic and Sleep Apnea Surgical Techniques - Kountakis, Stilianos E.; Önerci, T. Metin (Springer Berlin Heidelberg : Imprint: Springer, 2007)
As technology advances, practicing or training otolaryngologists register in educational courses to refresh their surgical skills and stay abreast of these changes. While information is becoming available in several journals, there is a definite need for a single surgical atlas-like book that contains precise descriptions of the surgical techniques used in rhinology and sleep apnea surgery. Each chapter was written by surgeons with extensive experience in each topic who have already published on the specific procedure described. Each chapter contains diagrammatic or illustrative descriptions of surgical techniques and provides tips and pearls of wisdom to avoid complications when the procedures are performed. This comprehensive work of surgical information serves as a valuable resource for otolaryngologists in training to augment their surgical education and for practicing otolaryngologists as a review source to best approach the surgical pathologies they encounter in their practice of rhinology and treatment of sleep apnea.